APPLICATIONS WITH VISUAL BASIC FINANCIAL STATEMENTS AT PT. ARIMI MANDIRI - Mochamad Rachim Abdul Arif; Ir. Fitri Sjafrina, MM (Jurnal Sistem Informasi, 2004)
The financial report is a product of the end of the accounting process that is used as adecision determining whether external or internal.The financial statements consist of a list of the profit - loss of capital and balancesheet changes. The financial report is closely related to the transaction in a way so asto be worthy of a report to be presented and meet the demands of stakeholders.On the application of financial reporting have created penulias three forms. On themain form to display the form of processing a forecast, daily transaction journal form,displays the form of a report on the form and for printing reports. In the formprocessing estimates are used to enter a name and its nominal estimates. Dailytransaction journal form used to enter daily transactions.To the officer who makes the financial statements must understand the basics ofaccounting, how you can operate the existing Windows operating system and has aminimum specification of hardware and software.